Efficacy and harm of pharmacological prevention of acute mountain sickness: quantitative systematic review - Dumont, Lionel (British Medical Journal, 2000)
OBJECTIVE: To quantify efficacy and harm of pharmacological prevention of acute mountain sickness. DATA SOURCES: Systematic search (Medline, Embase, Cochrane Library, internet, bibliographies, authors) in any language, up to October 1999. STUDY SELECTION: Randomised placebo controlled trials. DATA EXTRACTION: Dichotomous data on efficacy and harm from 33 trials (523 subjects received 13 different interventions, 519 a placebo). DATA SYNTHESIS: At above 4000 m the mean incidence of acute mountain sickness with placebo was 67% (range 25% to 100%); incidence depended on the rate of ascent, but not on the altitude or the mode of ascent. Across all ascent rates, dexamethasone 8-16 mg prevented acute mountain sickness (relative risk 2.50 (95% confidence interval 1.71 to 3.66); number needed to treat (NNT) 2.8 (2.0 to 4.6)), without evidence of dose responsiveness. Acetazolamide 750 mg was also efficacious (2.18 (1.52 to 3.15); NNT 2.9 (2.0 to 5.2)), but 500 mg was not. In two trials, adverse reaction (including depression) occurred after dexamethasone was stopped abruptly (4.45 (1.08 to 18); NNT 3.7 (2.5 to 6.9)). With acetazolamide, paraesthesia (4.02 (1.71 to 9.43); NNT 3.0 (2.0 to 6.0)) and polyuria (4.24 (1.92 to 9.37); NNT 3.6 (2.5 to 6.2)) were reported. Data were sparse on nifedipine, frusemide (furosemide), dihydroxyaluminium-sodium, spironolactone, phenytoin, codeine, phenformin, antidiuretic hormone, and ginkgo biloba. CONCLUSIONS: At above 4000 m, with a high ascent rate, fewer than three subjects need to be treated with prophylactic dexamethasone 8-16 mg or acetazolamide 750 mg for one subject not to experience acute mountain sickness who would have done so had they all received a placebo. Acetazolamide 500 mg does not work.